Population Change in Europe, the Middle-East and North Africa Beyond the Demographic Divide - Matthijs, Koenraad (International Population Studies, 2015)
Current demographic trends raise new questions, challenges and controversies. Comparing demographic trends in Europe and the NAME-region (North Africa and the Middle East), this book demonstrates how population change interacts with changing economic landscapes, social distinctions and political realities. A variety of drivers contribute to demographic change in the various regions and countries considered, such as family policies, economic realities, the impact of educational differentials and the attitudes towards marriage. On the macro-level the new trends are restructuring the age composition of populations and are reshaping the life courses of individuals and families. In turn, the impact demographic forces have on the organisation of labour markets, on fiscal policies, on the care of the elderly, on migration flows and on political changes can be quite radical. Chapter 1 of this book is freely available as a downloadable Open Access PDF under a Creative Commons Attribution-Non Commercial-No Derivatives 3.0 license. https://s3-us-west-2.amazonaws.com/tandfbis/rt-files/docs/Open+Access+Chapters/9781472439543_oachapter1.pdf